2016
DOI: 10.4103/1117-1936.190344
|View full text |Cite
|
Sign up to set email alerts
|

Oral health knowledge, awareness and associated practices of pre-school children′s mothers in Greater Noida, India

Abstract: The study participants exhibited poor knowledge and attitude towards their child's oral heath which was leading to the adoption of poor oral health practices by these mothers. Thus, to improve the oral health of children, appropriate practices and measures should be promoted among their parents/guardians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
19
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 10 publications
9
19
0
3
Order By: Relevance
“…In this study, about 46% of parents could identify the importance of adding fluoride to toothpaste. These results were similar to a study by Sehrawat et al (2016) [2] from India, who found that only 43% of the mothers knew that their toothpaste had fluoride. This result was contrasted by a study conducted by Jain et al (2014) [20].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, about 46% of parents could identify the importance of adding fluoride to toothpaste. These results were similar to a study by Sehrawat et al (2016) [2] from India, who found that only 43% of the mothers knew that their toothpaste had fluoride. This result was contrasted by a study conducted by Jain et al (2014) [20].…”
Section: Discussionsupporting
confidence: 91%
“…The knowledge and awareness of parents of their children's oral health is a fundamental component that generates a preventive measure thus, leading to establishing a sound oral health status of their children [1]. Moreover, lack of parents' knowledge and awareness of their oral health will also affect their children future oral health attitudes and practices that they adopt which will be carried over into adulthood [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…First, the rapid development of China’s economy has changed lifestyles and diet structures among its inhabitants, and the overconsumption of refined and high-sugar foods has increased the risk of malocclusion 38 , 39 . Second, a lack of proper oral hygiene knowledge, attitudes or behaviors among parents has likely contributed to the increasing prevalence of malocclusion among children 40 . For example, there is a general misunderstanding that malocclusion in primary dentition is temporary and should resolve with the eruption of permanent teeth.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Maternal role in promoting their children's oral habits and health has been emphasized. [7][8][9] Despite possible shift of role and responsibility in their family, 10 mothers still play an essential role in shaping their children's lifestyle, particularly their oral health. 7,9 Instrument to Measure Maternal Knowledge and Attitude Suryanti, Setiawan…”
Section: Introductionmentioning
confidence: 99%